The Patellofemoral Joint State of the Art in Evaluation and Management - Gobbi, Alberto; Espregueira-Mendes, João; Nakamura, Norimasa (Springer Berlin Heidelberg : Imprint: Springer, 2014)
A comprehensive and thorough selection of contributions from across the world, this book aims to review the current state-of-the-art in assessment and management of the patellofemoral joint. While featuring a wide range of surgical techniques for different pathologies, detailed attention is also devoted to conservative treatment and approaches involving mesenchymal stem cells, autologous chondrocyte implantation, platelet-rich plasma, and pulsed electromagnetic fields. Anatomy, clinical examination, and methods of evaluation are discussed, and individual chapters address important miscellaneous topics, including rehabilitation, complications of surgery, injuries in specific patient populations, and scoring systems. Though patellofemoral joint pathology is a frequent clinical problem, its management remains challenging for the orthopaedic surgeon. Conceived at the ISAKOS Congress held in Toronto in June 2013 as a small booklet, this work quickly turned into a major project involving more than 35 authors worldwide. The editors believe that this book will be of great value to orthopaedic doctors to improve understanding, diagnosis, and treatment of future patients.